2019
DOI: 10.1111/ppa.13029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in tolerant and susceptible potato cultivars in response to Spongospora subterranea f. sp. subterranea tuber infection

Abstract: Powdery scab caused by Spongospora subterranea f. sp. subterranea (Sss) has recently become one of the most devastating potato diseases of economic importance in South Africa. The use of resistant cultivars has long been considered the most effective and sustainable strategy to manage the pathogen. However, little is known about the molecular mechanisms underlying resistance of potato tubers to Sss. Using RNA-sequencing (RNA-seq), 2058 differentially expressed genes (DEGs) were identified from two potato culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In total, 9,730 and 12,732 (7,490 were full-length) proteins were predicted for P. brassicae and S. subterranea, respectively (Schwelm et al, 2015). Lekota et al (2019) analysed the responses of susceptible and resistant potato cultivars to S. subterranea infection and identified several defence−response genes that showed contrasting expression patterns between the susceptible and resistant cultivars. There are several other examples of the interaction between plasmodiophorids and their hosts (Barr et al, 1995;Zhao et al, 2017;Galindo-González et al, 2020;Ji et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In total, 9,730 and 12,732 (7,490 were full-length) proteins were predicted for P. brassicae and S. subterranea, respectively (Schwelm et al, 2015). Lekota et al (2019) analysed the responses of susceptible and resistant potato cultivars to S. subterranea infection and identified several defence−response genes that showed contrasting expression patterns between the susceptible and resistant cultivars. There are several other examples of the interaction between plasmodiophorids and their hosts (Barr et al, 1995;Zhao et al, 2017;Galindo-González et al, 2020;Ji et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite VGGRU-1 and VRM (Gg) 1 having different MYMV infection responses, 275 common DEGs were found in both mungbean genotypes. Previous studies have shown the advantage of focusing on the common DEGs between the resistant and susceptible genotypes to discover the possible candidate resistance genes in various diseases [15,22]. Therefore, we were mainly focused on 275 common DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of second and third-generation sequencing technologies, comparative transcriptome analysis through RNA sequencing (RNA seq) is the most popular method for detecting DEGs between two models [10][11][12][13]. Moreover, transcriptome analysis provides detailed information to understand the dynamics of interaction between the host and pathogen [14,15]. By comparing the transcriptome data from the pathogen-infected and control, countless studies have been attempted to elucidate the complete details of the genes and pathways involved in the molecular mechanism of resistance to pathogens [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Existe gran variabilidad genética de papa criolla (S. tuberosum grupo phureja) de buena aceptación en el mercado, por presentar características deseables para la culinaria e industria así mismo este grupo presenta mayor cantidad de proteína en comparación al grupo tuberosum, también buenos contenidos Fe, Zn y antioxidantes como vitamina C y fenoles (Ñustez y Rodríguez, 2020). Por otra parte, se han encontrado materiales con tolerancia a diferentes enfermedades como: tizón tardío (Phytophthora infestans) (Monteros y Delgado, 2021), virus del amarillamiento de venas (Torrance et al, 2020), marchitez bacteriana (Ralstonia solanacearum) (Lopes et al, 2021), sarna polvosa (Spongospora subterranea) (Lekota et al, 2019) y costra negra (Rhizoctonia solani) (Zhang et al, 2021). De ahí que estas características del grupo phureja constituyen el recurso genético para futuras investigaciones.…”
Section: Introductionunclassified